2014
DOI: 10.1002/chem.201400079
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Amyloid Fibril Growth and Dissolution of Amyloid Fibrils by Curcumin–Gold Nanoparticles

Abstract: Inhibition of amyloid fibrillation and clearance of amyloid fibrils/plaques are essential for the prevention and treatment of various neurodegenerative disorders involving protein aggregation. Herein, we report curcumin-functionalized gold nanoparticles (Au-curcumin) of hydrodynamic diameter 10-25 nm, which serve to inhibit amyloid fibrillation and disintegrate/dissolve amyloid fibrils. In nanoparticle form, curcumin is water-soluble and can efficiently interact with amyloid protein/peptide, offering enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(142 citation statements)
references
References 66 publications
2
140
0
Order By: Relevance
“…In line with these observations, several research groups have studied the effect of small molecule inhibitors on preformed aggregates and oligomers in detail1416171819. Previous studies showed that these molecules bind to pre-fibrillar aggregates, oligomers or fibrils and caused destabilization of aggregates or alters the amyloidogenic pathway27707172. In the current study, when the effect of curcumin and its analogs was tested on the preformed fibrils of α-Syn, it was found that none of these compounds affected the major protein secondary structure (β-sheet) within fibrils, as determined by CD or FTIR (Figs S3 and S4), however, effectively decreased the exposed hydrophobic surface on the fibrils (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In line with these observations, several research groups have studied the effect of small molecule inhibitors on preformed aggregates and oligomers in detail1416171819. Previous studies showed that these molecules bind to pre-fibrillar aggregates, oligomers or fibrils and caused destabilization of aggregates or alters the amyloidogenic pathway27707172. In the current study, when the effect of curcumin and its analogs was tested on the preformed fibrils of α-Syn, it was found that none of these compounds affected the major protein secondary structure (β-sheet) within fibrils, as determined by CD or FTIR (Figs S3 and S4), however, effectively decreased the exposed hydrophobic surface on the fibrils (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…[6][7][8][9][10][11][12] For instance, amino-modied polystyrene NPs have both acceleration and retardation effects on the Ab brillation process depending on the concentration and coverage of monomers on the particle surfaces. In recent years, the effect of different types of NPs on brillation process, either promoting or inhibiting, has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Similar curcumin-loaded PLGA nanoparticles (80-120 nm mean diameter) confirm lack of toxicity, and protect human SK-N-SH neuroblastoma cells from H 2 O 2 -induced elevation of ROS and consumption of glutathione [186]. Curcumin-functionalized, Si-coated, amide/ ester-connected Au nanoparticles (6.11, Figure 6.5, 10-25 nm hydrodynamic diameter) preferentially inhibit the elongation of Ab 40 oligomers, and promote the disaggregation of Ab 40 fibrils [187]. Ab 40 fibrils disaggregated by Au-supported curcumin are less neurotoxic on mouse neural crest-derived neuro2a cells than either native Ab 40 fibrils or soluble curcumin-disassembled Ab 40 fibrils [187].…”
Section: Interfering With (Neuro)toxic Tau Species In the Aggregationmentioning
confidence: 95%
“…Curcumin-functionalized, Si-coated, amide/ ester-connected Au nanoparticles (6.11, Figure 6.5, 10-25 nm hydrodynamic diameter) preferentially inhibit the elongation of Ab 40 oligomers, and promote the disaggregation of Ab 40 fibrils [187]. Ab 40 fibrils disaggregated by Au-supported curcumin are less neurotoxic on mouse neural crest-derived neuro2a cells than either native Ab 40 fibrils or soluble curcumin-disassembled Ab 40 fibrils [187].…”
Section: Interfering With (Neuro)toxic Tau Species In the Aggregationmentioning
confidence: 99%